Why not ask for help when I need it? Obstacles to the search for institutional academic support (IAS) in Chilean universities - Lobos Guerrero, Constanza; Gallardo, Gonzalo; Valenuzela, Jorge (Education Policy Analysis Archives, 2021)
Despite the global interest of universities in developing academic support mechanisms for their students, those who need these resources most don’t always use them. This phenomenon represents the greatest global challenge to institutionalized academic support services. This is also the case in Chile, where university enrollment has been consistently increasing. In this context, it is pertinent to consider the experience and perceptions of the university students themselves in order to identify obstacles to access and use of institutional academic support. From 25 individual interviews with university students in different regions (Metropolitan, Magallanes, Valparaíso and Araucanía), a focus group in the Metropolitan Region and a review of relevant literature, we identified factors that, from the student perspective, would limit their search for academic support. The results show obstacles in accessing academic support at three levels: first, obstacles of a socio-cultural nature, originating beyond the institutions with an impact on practices and discourses; institutional barriers to the search for help, created in each academic community; and finally, individual limitations, coming from previous experiences and learning trajectories of each subject. Finally, this article discusses these results, and poses educational policy changes for the success of institutional academic support.